The Role of Extracellular Vesicles in the Developing Brain: Current Perspective and Promising Source of Biomarkers and Therapy for Perinatal Brain Injury - Gamage, Teena K. J. B.; Fraser, Mhoyra (Frontiers in Neuroscience, 2021)
This comprehensive review focuses on our current understanding of the proposed physiological and pathological functions of extracellular vesicles (EVs) in the developing brain. Furthermore, in recent years, EVs have attracted great interest as potential novel cell-free therapeutics. Here we describe the advances in the knowledge of stem-cell- and astrocyte-derived EVs in relation to their potential for protection and repair following perinatal brain injury. This review identified 13 peer-reviewed studies evaluating the efficacy of EVs in animal models of perinatal brain injury; 12/13 utilised mesenchymal stem cell-derived EVs (MSC-EVs) and 1/13 utilised astrocyte-derived EVs. Animal model, method of EV isolation and size, route, timing, and dose administered varied between studies. Notwithstanding, EV treatment either improved and/or preserved perinatal brain structures both macroscopically and microscopically. Additionally, EV treatment modulated inflammatory responses and improved brain function. Collectively this suggests EVs can ameliorate, or repair damage associated with perinatal brain injury. These findings warrant further investigation to identify the optimal cell numbers, source, and dosage regimens of EVs, including long-term effects on functional outcomes.